VARIATION OF NITROGEN USE EFFICIENCY FROM MINERAL FERTILIZER ASSOCIATED WITH SOME FOLIAR TREATMENT - Gabriela MACRA; Florin SALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study evaluated the variation in the efficiency of nitrogen use from mineral fertilizers, associated with foliar fertilization in wheat, based on biological yield. Two specific indicators (Agronomic Efficiency - AE, Partial Factor Productivity - PFP) were calculated to quantify the efficiency of nitrogen use. The study was organized within the Didactic and Experimental Resort, BUASVM Timisoara. The 'Alex' wheat cultivar was cultivated, under the conditions of a chernozem type soil, medium fertility, and non-irrigated culture system. The 2020 – 2021 agricultural year was taken into account. Biological yield (BY, g m-2) was evaluated at physiological maturity (BBCH code 9, Senescence). Polynomial models of the 2nd degree described the variation of BY in relation to nitrogen (N) on each level of foliar fertilization (Super Fifty – SF), in differentiated conditions of statistical certainty (p<0.05 for the SF2 variant). There was an increasing variation in the AE and PFP values associated with foliar fertilization (SF), up to the level of SF2 and SF3 variants (2 – 3 L ha-1), followed by a decreasing trend. The regression analysis led to obtaining an equation-type mathematical model that described the BY variation in relation to N and SF, as a direct and interaction effect, under statistical safety conditions (p<0.001, R2=0.957). Based on the values of the obtained equation coefficients, the optimal doses were calculated (xopt=137.05 kg ha-1N active substance, yopt=2.92 L ha-1 SF, concentration 1.168 %).